Psychologically Comfortable Educational Environment for Children with Attention Deficit and Hyperactivity Disorder - Nikolaeva A. D. (Psychologically Safe Educational Environment: Design Problems and Development Prospects, 2020)
special characteristics of students with ADHD can make it difficult to learn at school and lead to a variety of social and adaptive problems in later life. To date, a large amount of practical material has been accumulated to create a psychologically comfortable and safe educational environment for children with ADHD. The article deals with the competent organization of the process of teaching this category of students in the General education system. The article analyzes the features of planning the educational process, organization of the student's workplace in the classroom, the implementation of his motor activity, the system of rewards and rewards, and feedback on the child's behavior.
Keywords: учебный процесс; learning process; синдром дефицита внимания и гиперактивности; условия обучения; attention deficit and hyperactivity disorder; learning environment